Impact of Patient-Selected Care Buddies on Adherence to HIV Care, Disease Progression, and Conduct of Daily Life Among Pre-antiretroviral HIV-Infected Patients in Rakai, Uganda: A Randomized Controlled Trial. (1st September 2015) - Nakigozi, Gertrude; Makumbi, Fredrick E.; Bwanika, John B.; Atuyambe, Lynn; Reynolds, Steven J.; Kigozi, Godfrey; Nalugoda, Fred; Chang, Larry W.; Kiggundu, Valerian; Serwadda, David; Wawer, Maria J.; Gray, Ronald H.; et al.
Abstract : Background: Data are limited on effects of household or community support persons ("care buddies") on enrollment into and adherence to pre-antiretroviral HIV care. We assessed the impact of care buddies on adherence to HIV clinic appointments, HIV progression, and conduct of daily life among pre-antiretroviral therapy (pre-ART) HIV-infected individuals in Rakai, Uganda. Methods: A total of 1209 HIV-infected pre-ART patients aged ≥15 years were randomized to standard of care (SOC) (n = 604) or patient-selected care buddy (PSCB) (n = 605) and followed at 6 and 12 months. Outcomes were adherence to clinic visits, HIV disease progression, and self-reported conduct of daily life. Incidence and prevalence rate ratios and 95% confidence intervals (CIs) were used to assess outcomes in the intent-to-treat and as-treated analyses. Results: Baseline characteristics were comparable. In the intent to treat analysis, both arms were comparable with respect to adherence to CD4 monitoring visits [adjusted prevalence risk ratio (adjPRR), 0.98; 95% CI: 0.93 to 1.04; P = 0.529], and ART eligibility (adjPRR, 1.00; 95% CI: 0.77 to 1.31; P = 0.946). Good conduct of daily life was significantly higher in the PSCB than the SOC arm (adjPRR, 1.08; 95% CI: 1.03 to 1.13; P = 0.001). More men (61%) compared with women (30%) selected spouses/partners as buddies ( P < 0.0001). Twenty-two percent of PSCB arm participants discontinued use of buddies. Conclusions: In pre-ART persons, having care buddies improved the conduct of daily life of the HIV-infected patients but had no effect on HIV disease progression and only limited effect on clinic appointment adherence.